2016
DOI: 10.1016/j.ejmech.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

O-alkylhydroxylamines as rationally-designed mechanism-based inhibitors of indoleamine 2,3-dioxygenase-1

Abstract: Indoleamine 2,3-dioxygenase-1 (IDO1) is a promising therapeutic target for the treatment of cancer, chronic viral infections, and other diseases characterized by pathological immune suppression. Recently important advances have been made in understanding IDO1’s catalytic mechanism. Although much remains to be discovered, there is strong evidence that the mechanism proceeds through a heme-iron bound alkylperoxy transition or intermediate state. Accordingly, we explored stable structural mimics of the alkylperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…We presume that the accuracy of the methylene blue-ascorbate regeneration system to keep IDO1 in its active state (Fe 2+ ) could be the primary reason for the differences in the inhibitory activity values between the pDMAB-and HPLC-based methods. 8,14 The HPLC-based assay also showed that monoamino substituted dipyrazolopyran derivative 4l displayed strongest inhibitory activity (IC 50 = 78 nM) among all the investigated compounds.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…We presume that the accuracy of the methylene blue-ascorbate regeneration system to keep IDO1 in its active state (Fe 2+ ) could be the primary reason for the differences in the inhibitory activity values between the pDMAB-and HPLC-based methods. 8,14 The HPLC-based assay also showed that monoamino substituted dipyrazolopyran derivative 4l displayed strongest inhibitory activity (IC 50 = 78 nM) among all the investigated compounds.…”
mentioning
confidence: 91%
“…Figure 1B showed that in the absence of compound the deoxy-ferrous-IDO1 enzyme displayed Soret and Q-band at 421 and 556 nm. 14 In the presence of compounds, 4j and 4l the Soret band (421 nm) got blue-shifted, and new Q bands appeared around 520/550 nm ( Figure 1B). This indicates their probable binding to the Fe 2+ -IDO1 enzyme.…”
mentioning
confidence: 96%
See 3 more Smart Citations